Events, Time and the Simple Form - Hirtle, Walter (Revue québécoise de linguistique, 1988)
AbstractThis is an attempt to discern more clearly the underlying or POTENTIAL meaning of the simple form of the English verb, described in Hirtle 1967 as 'perfective'. Vendler's widely accepted classification of events into ACCOMPLISHMENTS, ACHIEVEMENTS, ACTIVITIES, and STATES is examined from the point of view of the time necessarily contained between the beginning and end of any event, i.e. EVENT TIME as represented by the simple form. This examination justifies the well known dynamic/stative dichotomy by showing that event time is evoked in two different ways, that, in fact, the simple form has two ACTUAL significates. Further reflection on the difference between the two types thus expressed—developmental or action-like events and non-developmental or state-like events—leads to the conclusion that the simple form provides a representation of the time required to situate all the impressions involved in the notional or lexical import of the verb.